Writing women's space : changing reflections on gender and identity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Creative Writing at Massey University, Manawatū, New Zealand - Offord, Rachel Joy (Massey University, 2022)
Virginia Woolf challenged her gendered lack of access to spaces through her writing and essays, becoming an important feminist voice who substantiated women’s existence and questioned the social construction of identity. Challenging power dynamics that limit access to spaces by creating counter-sites and that press at the borders can produce new ideas and perspectives. Michel Foucault described these transformative spaces as heterotopias. Using the concept of Foucault’s heterotopias to explore Woolf’s “The Lady in the Looking Glass: A Reflection” (1928) alongside A Room of One’s Own (2015 [1929]) provides a useful lens for looking at how Woolf manipulated space to transform ways of seeing women and make us look at ourselves. In contemporary environments, social media has become a particularly powerful space for marginalised groups to not only share information and support each other but to imagine new worlds and create movements for change. In heterotopic spaces such as fiction and online environments, we can deconstruct gender binaries, substantiate the existence of marginalised people and choose our own identities. The usefulness of heterotopic spaces and their power to subvert dominant power structures allow marginalised narratives to be heard.
Keywords: 360201 Creative writing (incl. scriptwriting)